Pengaruh Keputusan Investasi, Pendanaan, Kebijakan Dividen, Kepemilikan Manajerial, Dan Institusional Terhadap Nilai Perusahaan - Reni Yendrawati (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2013)
Optimization of the company's value can be achieved through the implementation of the financial management function. This study aims to verify empirically the effect of investment decisions, financing decisions, divident policy, management ownership,and institutional ownership on the firm value. Firm value in this research measured by Price Book Value (PBV). The study used purposive sampling method for determining the number of sample on all of company listed in Indonesia Stock Exchange (IDX) period 2008 to2011. Hypothesis test uses multiple regression analysis. The result shows that divident policy, management ownership,and institutional ownership positively affects the firm value. While investment decisions and financing decisions did not effects the firm value.